تعليقات المعلم نحو مهارة الكتابة لطلاب الفصل الحادي عشر بالمدرسة السلفية الثانوية الإسلامية تانجولانجين سيدوارجو - Akbar, Abdurrosyid; Huda, Hisbullah (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2018)
The results of this study analyze "The impact of teacher comments on the writing skills of eleventh grade students at Salafiyah Islamic Middle School, Tangulangin Sidoarjo". The results of the questions answer the question about whether there is an influence of teacher comments on the writing skills of eleventh grade students of the Salafiyah Islamic Middle School of Tungulangin Sidwarjo. Researchers used qualitative and descriptive methods. As for the method of collecting data by means of observation, interviews and documents. This research is presented in the form of reports and descriptions, then arranged in the form of descriptive research results in the form of interactive analysis. The results of data analysis in this study are that teacher comments with scribbles in the form of written justification comments and reinforcement comments have a positive impact on improving students' writing skills as evidenced by student worksheets